2017
DOI: 10.1007/s12630-017-0938-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for delirium after cardiac surgery: a historical cohort study outlining the influence of cardiopulmonary bypass

Abstract: Purpose Cardiopulmonary bypass (CPB) induces a significant inflammatory response that may increase the risk for delirium. We hypothesized that exposure to CPB during coronary artery bypass grafting surgery would correlate with an increased risk of delirium and would be associated with several other outcomes. Methods We reviewed clinical data from two databases at our medical center, the Cardiac Surgery Perioperative Outcomes Database and the Society of Thoracic Surgeons Database. Patients undergoing elective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 42 publications
2
25
0
3
Order By: Relevance
“…The pathogenesis of delirium in cardiac surgery patients is uncertain, but neuroinflammation exacerbated by the use of CPB may play a role . Overall, 177 (177/202 [87.6%]) participants had CPB during surgery (melatonin 86.7% vs placebo 88.5%; χ 2 = .14; P = 710) in our sample, but exposure to this was not associated with an increase in delirium risk (OR = 1.44; 95% CI = .46‐4.43).…”
Section: Resultsmentioning
confidence: 73%
“…The pathogenesis of delirium in cardiac surgery patients is uncertain, but neuroinflammation exacerbated by the use of CPB may play a role . Overall, 177 (177/202 [87.6%]) participants had CPB during surgery (melatonin 86.7% vs placebo 88.5%; χ 2 = .14; P = 710) in our sample, but exposure to this was not associated with an increase in delirium risk (OR = 1.44; 95% CI = .46‐4.43).…”
Section: Resultsmentioning
confidence: 73%
“…Cognitive performance 7 days after surgery followed a similar trend: anaortic OPCAB had the lowest incidence of cognitive decline (9.5%), followed by CO 2 field flooding (28.1%), and then conventional OPCAB (34.4%), mirroring previous observational studies. 4 Interestingly, the relative ratio of delirium to postoperative cognitive decline followed a similar pattern (76% vs 85% vs 95%) for anaortic, carbon dioxide field flooding, and conventional OPCAB, respectively.…”
Section: Delirium and Postoperative Cognitive Dysfunction (Pocd)mentioning
confidence: 74%
“…Research groups have shown that patients after valve replacement surgery have significantly worse cognitive functioning than patients following coronary artery bypass grafting (CABG) surgery 7 8. Combined surgeries, often involving longer bypass times, may also increase the risk of delirium 9. Procedures requiring entry into the heart involve increased embolic load, generating the possibility of postoperative neurological impairment 10…”
Section: Introductionmentioning
confidence: 99%